2004
DOI: 10.1097/01.ju.0000145222.94455.73
|View full text |Cite
|
Sign up to set email alerts
|

Potency, Continence and Complications in 3,477 Consecutive Radical Retropubic Prostatectomies

Abstract: Purpose: We report results in a series of 3,477 consecutive patients treated with anatomical nerve sparing radical retropubic prostatectomy (RRP) in terms of recovery of erectile function, urinary continence and postoperative complications.Materials and Methods: From May 1983 through February 2003, 1 surgeon (WJC) performed anatomical RRP using a unilateral or bilateral nerve sparing modification when possible. Urinary continence and recovery of erections were evaluated in men with a minimum followup of 18 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
295
5
20

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 515 publications
(342 citation statements)
references
References 23 publications
22
295
5
20
Order By: Relevance
“…23 As shown in several other studies, patients who had undergone nerve-sparing RP have a greater chance to regain sexual function than patients who had undergone non-nerve-sparing RP. 9,10,24 However, even 1 year after nerve-sparing RP, 66% of patients had a severe form of ED, 27% of patients had regained at least some degree of EF and only 7% of patients had regained full EF. Thus, postsurgical improvement of EF does not mean a full convalescence of presurgical EF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 As shown in several other studies, patients who had undergone nerve-sparing RP have a greater chance to regain sexual function than patients who had undergone non-nerve-sparing RP. 9,10,24 However, even 1 year after nerve-sparing RP, 66% of patients had a severe form of ED, 27% of patients had regained at least some degree of EF and only 7% of patients had regained full EF. Thus, postsurgical improvement of EF does not mean a full convalescence of presurgical EF.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Thus, we expect significantly better sexual functioning in patients who had undergone nerve-sparing vs non-nerve-sparing surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Patients between ages 40 years and 49 years reported rates of erectile function recovery as high as 92%. 13 In addition to patient age, it recently was demonstrated that a difference in age between a patient and their partner is associated linearly with better sexual outcome after RP. 15 A difference in patient and partner age as great as 20 years was associated with a roughly 3.5-fold increased erectile function recovery rates compared with patients who were the same age as their partners (90% vs 25%; P < .001).…”
Section: Patient and Partner Agementioning
confidence: 99%
“…Several trials have indicated that the best postoperative potency rates are obtained in the younger patient population. [11][12][13][14] Younger patients are more likely to have better preoperative erectile function and to be more interested in sexual recovery after surgery. [11][12][13][14] Patients between ages 40 years and 49 years reported rates of erectile function recovery as high as 92%.…”
Section: Patient and Partner Agementioning
confidence: 99%
See 1 more Smart Citation